Business cycles, core and periphery in monetary unions: Comparing Europe and North America - Ferreira-Lopes, Alexandra (2022)
We compare Europe with the USA and Canada as regards business cycle synchronization and core-periphery patterns. A long sample (1950-2005) makes it possible to study how these aspects have evolved over time. Results support the economic viability of EMU. Average cyclical correlations among European countries have risen signicantly, reaching levels close to, or even higher than, those of North American regions. Applying fuzzy clustering to the analysis of core-periphery issues, we nd Europe to actually outperform North America: the core-periphery divide is milder, and peripheral status seems generally less protracted.